THE EFFECT OF INTERNAL MARKETING STRATEGY IN ORGANIZATIONAL COMMITMENT A study in schools in Portugal - Silva, Mariana da Cruz (2021)
Dissertação de Mestrado em Marketing apresentada à Faculdade de Economia